Monte Carlo Calculations Supporting Patient Plan Verification in Proton Therapy - Lima, Thiago V. M.; Dosanjh, Manjit; Ferrari, Alfredo; Molineli, Silvia; Ciocca, Mario; Mairani, Andrea (Frontiers in Oncology, 2016)
Patient’s treatment plan verification covers substantial amount of the quality assurance (QA) resources, this is especially true for Intensity Modulated Proton Therapy (IMPT). The use of Monte Carlo (MC) simulations in supporting QA has been widely discussed and several methods have been proposed. In this paper we studied an alternative approach from the one being currently applied clinically at Centro Nazionale di Adroterapia Oncologica (CNAO). We reanalysed the previously published data (Molinelli et al. 2013), where 9 patient plans were investigated in which the warning QA threshold of 3% mean dose deviation was crossed. The possibility that these differences between measurement and calculated dose were related to dose modelling (Treatment Planning Systems (TPS) vs MC), limitations on dose delivery system or detectors mispositioning was originally explored but other factors such as the geometric description of the detectors were not ruled out. For the purpose of this work we compared ionisation-chambers measurements with different MC simulations results. It was also studied some physical effects introduced by this new approach for example inter detector interference and the delta ray thresholds. The simulations accounting for a detailed geometry typically are superior (statistical difference - p-value around 0.01) to most of the MC simulations used at CNAO (only inferior to the shift approach used). No real improvement were observed in reducing the current delta-ray threshold used (100 keV) and no significant interference between ion chambers in the phantom were detected (p-value 0.81). In conclusion, it was observed that the detailed geometrical description improves the agreement between measurement and MC calculations in some cases. But in other cases position uncertainty represents the dominant uncertainty. The inter chamber disturbance was not detected for the therapeutic protons energies and the results from the current delta threshold are acceptable for MC simulations in IMPT.